Answer:
x = -3 and y = 2 is the solution.
Explanation:
we have given system of equations:
6x+6y=-6 equation I
5x+y = - 13 equation II
we solve this system of equation by using elimination method.
multiplying the equation II by - 6.
(-6)5x + ( -6 )y = ( - 6 ) (- 13 )
-30 x - 6 y = 78 equation III
adding equation I and III we have
6x + 6y = - 6
-30x -6y =78
_____________
- 24 x = 72
x = - 3
substituting value of x in any of original equations and solve it for y.
we are putting the value of x in equation I and solve it for y
6( -3 )+ 6y = -6
-18 + 6y = -6
6y = 12
y = 2
so, x = -3 and y = 2 is the solution of given system of equations.